The physical geography of South America - Veblen, Thomas T., 1947-; Young, Kenneth R.; Orme, A. R. (Oxford regional environments., 2007)
The Physical Geography of South America, the eighth volume in the Oxford Regional Environments series, presents an enduring statement on the physical and biogeographic conditions of this remarkable continent and their relationships to human activity. It fills a void in recent environmental literature by assembling a team of specialists from within and beyond South America in order to provide an integrated, cross-disciplinary body of knowledge about this mostly tropical continent, together with its high mountains and temperate southern cone. The authors systematically cover the main components of the South American environment - tectonism, climate, glaciation, natural landscape changes, rivers, vegetation, animals, and soils. The book then presents more specific treatments of regions with special attributes from the tropical forests of the Amazon basin to the Atacama Desert and Patagonian steppe, and from the Atlantic, Caribbean, and Pacific coasts to the high Andes. Additionally, the continents environments are given a human face by evaluating the roles played by people over time, from pre-European and European colonial impacts to the effects of modern agriculture and urbanization, and from interactions with El Nino events to prognoses for the future environments of the continent.